LA SEQUENZA NUMIDICA NEL SUO CONTESTO GEOTETTONICO: UNA PROPOSTA DI ORDINE PALEOGEOGRAFICO (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
Numerous and much debated are the interpretations given through time far the Numidian Sequence and Lateral Facies in the different sectors of the Maghreb, Cordillera Chain and Southern Apennine. The Numidian Sequence can be schematically subdivided, in the regional context, into three main stratigraphical intervals. They can be found in two successions which are different far their palaeogeographic position. Moreover, are present some Lateral Facies in the external (Numidian like Sequence) and internal (Mixed Successions) palaeogeographical position in relation to Numidian Sequence. The Numidian Basin may be located, in agreement with most of the previous authors, at South of the European Paleomargin, towards the African Paleomargin, probably aver the Massylian and Ultra-Tellian p.p. palaeogeographic sectors (External Zones), more or less deformed. The Numidian Basin may represent an active Upper Oligocene-Early Miocene foredeep, relatively more external with respect to the "Maghrebian flysch basin", supplied by quartzose sands of saharian origin.
Keywords: Numidian Sequence; Lateral Facies; Upper Oligocene-Lower Miocene; Betic; Maghrebian and Southern Apennine Chains; Palaeogeography